PENERAPAN METODE PENCATATAN DAN PENILAIAN TERHADAP PERSEDIAAN BARANG MENURUT PSAK NO.14 PADA CV. METRO ELEKTRONIK DI KABUPATEN BERAU (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2017)
This study aims to know clearly the application of methods of recording and assessment of inventory on the CV. Metro Electronics in Berau in accordance with PSAK No.14. This writing uses a comparative descriptive analysis method with reference to PSAK No.14 on inventory.CV. Metro Electronics to assess its inventory using the LIFO method. Whereas, according to PSAK No.14: Inventory cost, shall be calculated using the first-in first-out formula (MPKP / FIFO) or weighted average. In the formula MPKP assumes the first purchased inventory item will be sold or used first therefore items left in the ending inventory are purchased or produced later. Therefore, it can be concluded that the method of valuation of inventory on CV. Metro Electronics is not in accordance with PSAK No.14 and means accepting the research hypothesis.